Design of walking and sitting aids for the elderly using the kano method - Muhamad Mukafi; Ahmad Dzulfikri (Universitas Mercu Buana, 2023)
Normal human growth with age in the process of life tries to adapt to environmental conditions. It is often found that those who experience a decrease in walking activity, this is due to decreased function of the muscles and limbs. A walker (Walker) is the right solution to help with their activities. The design development of walking aids (Walker) continues to be developed for the needs of consumers, especially the elderly and injured feet. The purpose of this product design, which is to facilitate Walker users in resting to sit after a long walk without having to look for a place to sit and is available directly with the Walker, besides that it can also be used as a wheelchair with the help of ot hers. The features needed can be identified based on the results of a questionnaire which is the basis for the design development of walkers (Walkers) that have been on the market. The output of the questionnaire was analyzed by noting important features using the Kano Method. The research results are in the form of two features, with categories in the form of attractive that need to be developed. The features in question are the addition of seats, backrests, and wheels.